Identification of Ureidocoumarin-Based Selective Discoidin Domain Receptor 1 (DDR1) Inhibitors via Drug Repurposing Approach, Biological Evaluation, and In Silico Studies - Ashraf K. El-Damasy; Hyun Ji Kim; Ahmed A. Al-Karmalawy; Radwan Alnajjar; Mohamed M. Khalifa; Eun-Kyoung Bang; Gyochang Keum (MDPI AG, 2024)
Discoidin domain receptor 1 (DDR1) kinase has emerged as a promising target for cancer therapy, and selective DDR1 inhibitors have shown promise as effective therapeutic candidates. Herein, we have identified the first coumarin-based selective DDR1 inhibitors via repurposing of a recent series of carbonic anhydrase inhibitors. Among these, ureidocoumarins 3a, 3i, and 3q showed the best DDR1 inhibitory activities. The m-trifluoromethoxy phenyl member 3q potently inhibited DDR1 with an IC50 of 191 nM, while it showed less inhibitory activity against DDR2 (IC50 = 5080 nM). 3q also exhibited favorable selectivity in a screening platform with 23 common off-target kinases, including BCR-ABL. In the cellular context, 3q showed moderate antiproliferative effects, while 3i, with the third rank in DDR1 inhibition, exerted the best anticancer activity with sub-micromolar GI50 values over certain DDR1-dependent cell lines. Molecular docking and MD simulations disclosed the putative binding mode of this coumarin chemotype and provided insights for further optimization of this scaffold. The present findings collectively supported the potential improvement of ureidocoumarins 3i and 3q for cancer treatment.